Gellan Gum-Based In Situ Hydrogels for Nasal Delivery of Polymeric Micelles Loaded with Risperidone - Bence Sipos; Mária Budai-Szűcs; Gábor Katona; Ildikó Csóka (Gels, 2025)
Nasal drug delivery faces numerous challenges related to the ineffectiveness of most nasal formulations without a mucoadhesive nature, prolonging residence time on the nasal mucosa. Another challenge is the low administrable dosage strength, which can be solved via nano-encapsulation techniques, including the utilization of polymeric micelles. In this study, gellan gum–cellulose derivative complex in situ gelling matrices were formulated to test their effect on the colloidal characteristics of polymeric micelles, their respective rheological behavior, and nasal applicability. It has been proven that these complex matrices can form gels upon contact with nasal fluid without disrupting the micellar structure. Changes in the drug release and permeation profile have been shown in a concentration-dependent manner to hinder the burst-like drug release profile of polymeric micelles. Formulations show concentration- and composition-dependent mucoadhesive features under nasal conditions. Most of the hydrogels possess a soft gel characteristic, making them suitable for nasal administration. In conclusion, this descriptive study provides useful insights for conscious, nasal dosage form design.